Potential of adenovirus‐mediated REIC/Dkk‐3 gene therapy for use in the treatment of pancreatic cancer. Issue 5 (May 2014) - Uchida, Daisuke; Shiraha, Hidenori; Kato, Hironari; Nagahara, Teruya; Iwamuro, Masaya; Kataoka, Junro; Horiguchi, Shigeru; Watanabe, Masami; Takaki, Akinobu; Nouso, Kazuhiro; Nasu, Yasutomo; Yagi, Takahito; et al.
Abstract Background and Aim The reduced expression in immortalized cells REIC/the dickkopf 3 (Dkk‐3) gene, tumor suppressor gene, is downregulated in various malignant tumors. In a prostate cancer study, an adenovirus vector carrying the REIC/Dkk‐3 gene (Ad‐REIC) induces apoptosis. In the current study, we examined the effects of REIC/Dkk‐3 gene therapy in pancreatic cancer. Methods REIC/Dkk‐3 expression was assessed by immunoblotting and immunohistochemistry in the pancreatic cancer cell lines (ASPC1, MIAPaCa2, Panc1, BxPC3, SUIT‐2, KLM1, and T3M4) and pancreatic cancer tissues. The Ad‐REIC agent was used to investigate the apoptotic effect in vitro and antitumor effects in vivo. We also assessed the therapeutic effects of Ad‐REIC therapy with gemcitabine. Results The REIC/Dkk‐3 expression was lost in the pancreatic cancer cell lines and decreased in pancreatic cancer tissues. Ad‐REIC induced apoptosis and inhibited cell growth in the ASPC1 and MIAPaCa2 lines in vitro, and Ad‐REIC inhibited tumor growth in the mouse xenograft model using ASPC1 cells. The antitumor effect was further enhanced in combination with gemcitabine. This synergistic effect may be caused by the suppression of autophagy via the enhancement of mammalian target of rapamycin signaling. Conclusions Ad‐REIC induces apoptosis and inhibits tumor growth in pancreatic cancer cell lines. REIC/Dkk‐3 gene therapy is an attractive therapeutic tool for pancreatic cancer.